Sistem Dinamis sebagai Alat Analisis dan Pengambilan Keputusan di Indonesia: Literature Review - Pamungkas, Iing; Akmal, Abdiel Khaleil; Irawan, Heri Tri; Syahputra, Rizki Agam; Ridha, Arrazy Elba; Zhaqiri, Hazdfi; Fadjrin, Sitti (Jurnal Industri dan Inovasi (INVASI), 2025)
This research aims to conduct a comprehensive literature review on the application of dynamic system simulation as a decision-making tool. This research is motivated by the complexity of modern problems that require appropriate analytical tools to support better decision-making. The method used in this research is a systematic literature review by following structured steps to ensure that this research is comprehensive and unbiased. The results of this study indicate that dynamic systems are powerful and relevant analytical tools across sectors. With its ability to model dynamic interactions and simulate future scenarios, dynamic systems can help stakeholders make better decisions and achieve more sustainable results in facing complex challenges in the modern era. This study also identifies several challenges in the application of dynamic system simulation, such as lack of awareness of its benefits, lack of expertise in building and analyzing simulation models, as well as limited in-depth research on its application in various contexts. Therefore, further research is needed to address these challenges and improve the application of dynamic system simulation in decision making.